Implementation of the 3R Waste Disposal (TPS-3R) program in Tanah Sareal District, Bogor City - Yudi Prakasa; Sri Wahyuni; Sata Yoshida Srie Rahayu (Indonesian Journal of Applied Environmental Studies, 2025)
Rapid population growth has generated significant environmental challenges, particularly in waste management, which remains a national strategic issue in Indonesia. Waste management is regulated under Law No. 18 of 2008 on Waste Management and strengthened through Presidential Regulation No. 97 of 2017, which outlines the National Policy and Strategy for Household Waste and Similar Waste Management. One approach to reducing household waste is the TPS-3R (Reduce, Reuse, Recycle) program, which emphasizes minimizing waste volumes and improving waste characteristics prior to disposal at final landfill sites (TPA). This study aims to evaluate the performance of the TPS-3R program in Bogor City in terms of its effectiveness in reducing household waste. The evaluation applied the CIPP model (Context, Input, Process, and Product). The findings show that the Context aspect is strong, as the program aligns with national regulations, has a clear legal foundation, and meets the objective of reducing waste at its source through community participation. The Input aspect is adequate but requires improvement: TPS-3R facilities generally meet basic standards; however, human resources are still limited, with managerial and technical roles often carried out concurrently, and maintenance funding remains insufficient. The Process aspect is also rated adequate: available facilities are only utilized at 50–70%, while training and capacity building for TPS-3R managers are conducted more than three times annually. Funding primarily relies on community contributions, government allocations, and revenues from recyclable products. The Product aspect shows partial success: TPS-3R facilities contribute to waste reduction and generate by-products that provide supplementary income, yet overall waste reduction targets outlined in the Regional Waste Management Strategy (Jakstrada) have not been fully met. In conclusion, optimizing both input and process components is crucial to enhance TPS-3R performance and achieve the national target of reducing waste by 30% by 2025.